Thermal performance of a PCB channel heat sink for LED light bulbs. (October 2015) - Jang, Daeseok; Park, Seung-Jae; Lee, Kwan-Soo
Highlights: The thermal performance of PCB as a heat sink for LED bulbs is analyzed. The cooling performance is improved by arranging parallel PCB as a channel. The heat transfer is optimized by balancing flow rates on external and internal PCB. The orientation effect on PCB channel was found to be 10% less than reference design. Abstract: In this study, the thermal performance of the printed circuit board (PCB) as a heat sink for the light-emitting diode (LED) bulb is analyzed. Cooling air is drawn through the bottom inlet of a case and exchanges heat from a vertically aligned PCB acting as a heat sink fin. The air then exits through a top outlet. Cooling performance is improved by arranging parallel PCBs to form a channel. Heat transfer is optimized by balancing cooling airflow rates on external and internal PCB surfaces, thereby reducing thermal resistance by 30% compared to previous designs. Cooling performance according to installation angle is investigated. The orientation effect on this channel design is determined to be 10% less than that of the reference design. Finally, the effect of PCB channel cooling performance on the LED bulb's life span is analyzed and shown to be 40% longer than that of the existing geometry.